2013
DOI: 10.1007/s11738-013-1360-4
|View full text |Cite
|
Sign up to set email alerts
|

Copper phytoextraction with willow (Salix viminalis L.) under various Ca/Mg ratios. Part 1. Copper accumulation and plant morphology changes

Abstract: This work reports a part of hydroponic experiment results concerning changes in Salix viminalis L. cv. 'Cannabina' morphology and physiology under stress conditions with different copper concentration levels and verifies our earlier results about the role of different Ca/Mg ratios in trace elements' accumulation efficiency. In this part, we present the copper accumulation and changes in willow biomass. Concentration of copper in roots, rods, shoots and leaves was analyzed with flame atomic absorption spectrome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 42 publications
1
8
0
Order By: Relevance
“…Our previous results indicated that the content of Cd, Cu, and Pb increased with increasing levels in the root zone. In this regard, Mleczek et al (2013) found a general increase in Cu accumulation in S. viminalis organs with increased Cu concentrations in the medium. Additionally, S. polaris organs treated with Cd have shown different concentrations between plant parts (Krajcarova et al, 2016).…”
Section: Resultsmentioning
confidence: 72%
See 1 more Smart Citation
“…Our previous results indicated that the content of Cd, Cu, and Pb increased with increasing levels in the root zone. In this regard, Mleczek et al (2013) found a general increase in Cu accumulation in S. viminalis organs with increased Cu concentrations in the medium. Additionally, S. polaris organs treated with Cd have shown different concentrations between plant parts (Krajcarova et al, 2016).…”
Section: Resultsmentioning
confidence: 72%
“…Moreover, Dos Santos Utmazian et al (2007) revealed that willow growth and phytoextraction efficiency were significantly dependent on the planted species, and that there were differences in plant biomass, metal tolerance, and metal phytoextraction of willow clones. In addition, BCF values of different organs (leaf, bark, shoots, and roots) of S. viminalis in Cu concentrations of different Ca/Mg ratios were estimated as weak in most cases and as moderate in some cases, particularly in roots (Mleczek et al, 2013).…”
Section: Resultsmentioning
confidence: 97%
“…The results were compared with the certified reference material NCS ZC 73030 from the China National Analysis Center for Iron & Steel 2014 and with reference solutions by Fluka assigned the symbols: Pb 16595, Cd 51994, Cr 02733, Ni 42242, Mn 63534, Zn 18827, Cu 38996, Fe 16596, and Co 119785.0100. Moreover, the following coefficients were calculated for cobalt determined in oat grain, straw, and roots: bioconcentration coefficient from the formula: (BCF) = C plant organ /C soil , translocation coefficient (TF) = C aerial parts /C roots , and transfer coefficient (TFr) = C plant /C soil , where C stands for cobalt content expressed in mg kg −1 (Ali et al 2013 ; Mleczek et al 2013 ). Moreover, tolerance index Ti was computed from the formula: Ti = biomass yield from a cobalt-polluted object / biomass yield from the control object.…”
Section: Methodsmentioning
confidence: 99%
“…Results presented efficiency of Cu accumulation in Salix purpurea 9 viminalis roots, shoots, bark, rods and leaves with information about changes in willow biomass were presented in Part 1. (Mleczek et al 2013 . A similar relationship was observed in the earlier studies on Cd and Pb accumulation , or Cu and Zn accumulation by Salix.…”
Section: Discussionmentioning
confidence: 99%